TRANSFER OF PROPERTY ASSETS - Vasilica NEGRUŢ (Challenges of the Knowledge Society)
Starting from the current jurisprudence on the transfer of property assets, in this article, using logical interpretation and also comparative analysis, we intend to investigate the conditions under which an asset from the private domain of the state can be transferred to its public or private domain of an administrative-territorial unit in its public domain, according to the law (article 863 letter d) of the Civil Code). Also, the analysis also concerns the transfer of an asset from the public domain to the private domain, under the conditions established by Law no. 213/1998 on publicly owned property. The recent amendments to this legislative act were also determined by the complex cases brought before the courts regarding the transfer of property assets. In conclusion, if the asset belongs (according to its purpose, to the national or local public use or interest) to the national or local public domain, then the transfer is carried out according to the procedure established by art. 9 of the Law no. 213/1998, respectively by an administrative act of an individual character, a decision of the Government or a local council. If the object is the exclusive object of public property of the state, according to an organic law, it is also possible by law to transfer the public domain of the state to that of an administrative - territorial unit. It is about the organic laws of modifying the organic law by which the assets have been declared the exclusive object of public property of the state.